Seismic response of a typical 3-legged jacket of fixed offshore platform in Malaysia due to Aceh earthquake - Nurul Nabila, Fazilan (2015)
A level of concern among engineers in Malaysia about the crucial aspect to consider the seismic response due to earthquake in structure design still low. Majority of buildings in Malaysia is been designing based on BS8110 .However, these standards do not have any requirements on seismic loads. Actually, Malaysia have experienced the earthquake tremors due to the neighboring countries, such as Indonesia which have experienced of seismological activities in the past few year. Thus, chance of Malaysia being jolted by at least one moderate earthquake cannot be ruled out. The purposes of this study is to estimate the earthquake ground motion due to earthquake in Aceh Indonesia for assessment of offshore platform in Malaysia. Besides, by doing this study, we could determine the vulnerability of existing offshore platform in Malaysia when subjected to loading from earthquake. The response of the fixed steel jacket offshore platform under earthquake loading (shear, displacement and bending moment) can be also determined. The region for interested offshore platform site is in Terengganu. All the environmental loads in Terengganu is given such as wave height, current velocity and wind speed are given. The ground motion acceleration from Aceh earthquake also be given. There are three type of seismic response analysis in this study which are free vibration analysis, time history analysis and response spectrum analysis. In free vibration analysis, 12 mode shape is analyses. For the response spectrum analysis, the analysis is based on response spectra of EuroCode 8.While for the time history analysis, is referring to the time history of Aceh’s earthquake in 2004. SAP2000 computer software is chosen to analyses the earthquake response to the steel jacket offshore platform. The steel structure is design according to EuroCode 3 standards.